2017
DOI: 10.1111/iej.12723
|View full text |Cite
|
Sign up to set email alerts
|

Failure of single‐unit restorations on root filled posterior teeth: a systematic review

Abstract: Afrashtehfar KI, Ahmadi M, Emami E, Abi-Nader S, Tamimi F. Failure of single-unit restorations on root filled posterior teeth: a systematic review. International Endodontic Journal, 50, 951-966, 2017. This systematic review investigated the failure rate of conventional single-unit restorations in root filled posterior permanent teeth. Two reviewers independently applied eligibility criteria, extracted data and assessed the quality of the evidence of each included study according to the Cochrane Collaboratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 67 publications
2
30
0
2
Order By: Relevance
“…A high percentage of the participants decided the need for cuspal coverage for ETT with a MO/DO cavity and thin axial walls (75% for molar and 96.7% for the premolar). This decision was consistent with a systematic review in which the failure rate was found to be reduced when such clinical situations were managed using cuspal coverage instead of using intracoronal restorations (Afrashtehfar, Ahmadi, et al, ). Scotti et al () found the remaining wall thickness to be a very important clinical parameter in the resistance of fracture in endodontically treated premolars and suggested that an axial wall thickness of less than 2 mm is an indication for cuspal coverage to improve the fracture resistance in maxillary premolars.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…A high percentage of the participants decided the need for cuspal coverage for ETT with a MO/DO cavity and thin axial walls (75% for molar and 96.7% for the premolar). This decision was consistent with a systematic review in which the failure rate was found to be reduced when such clinical situations were managed using cuspal coverage instead of using intracoronal restorations (Afrashtehfar, Ahmadi, et al, ). Scotti et al () found the remaining wall thickness to be a very important clinical parameter in the resistance of fracture in endodontically treated premolars and suggested that an axial wall thickness of less than 2 mm is an indication for cuspal coverage to improve the fracture resistance in maxillary premolars.…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, uncertainty in decision making were more likely to be reported for clinical situations of VT compared with clinical situations of ETT. This could be due to the lack of knowledge synthesis in the literature for deciding when cuspal coverage is needed for VT (Afrashtehfar, Emami, et al, ), compared with the available knowledge synthesis for ETT (Afrashtehfar, Ahmadi, et al, ; Goodacre & Spolnik, ; Smith & Schuman, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The treatment depends on the severity of the caries. If the tooth is still in good condition, a filling can be placed [45,46]. A root canal treatment is recommended for deep caries that has reached the pulp.…”
Section: Discussionmentioning
confidence: 99%